Balinese Traditional Agroforestry as Base of Watershed Conservation - I Gusti Diah Ayu Yuniti; Jhon Hardy Purba; Nanang Sasmita; Liris Lis Komara; Tomycho Olviana; I Made Kartika (Journal of Applied Agricultural Science and Technology, 2022)
Forests, traditional gardens and green spaces play an important role in regulating the water flow of an area. Along with the high demand for land in Bali for agriculture and tourism, many forest areas have been converted into hotels and settlements. Forest conversion has caused many problems such as erosion, soil fertility decreased, flora fauna extinction, floods, drought, global warming and the disturbing watershed, especially rivers for springs. The purpose of this study is the development of watershed conservation in Bali based on traditional agroforestry. The method that used is vegetation analysis. Calculation of the erosion amount using the USLE formula. Sampling was done by ten plots. The results showed that traditional agroforestry vegetation consisted of vertical and horizontal structures. The characteristic of traditional agroforestry is that dominant plants are distributed irregularly, thus creating a miniature structure like a forest. The vertical structure consists of trees, horizontal structure filled with species of garden plants and agriculture. Trees have roots spread intensively in the soil and reduce nutrient leaching. Land cover by vegetation protects the soil and erosion. The agroforestry has a role as an act of soil and water conservation. Traditional agroforestry land cover has a relatively low C coefficient (0.05-0.25) compared to other lands. The level of erosion hazard is low and moderate. Average erosion value of 55.01 t.ha-1.yr-1. This indicates that traditional agroforestry makes the soil have a higher ability to absorb water, thereby reducing surface runoff. Likewise, organic material that improves the water content capacity. In addition, water quality can be improved through the humus filter function. During a long dry season, there is a drought due to low rainfall, but rivers and springs were able to supply water for the peoples daily needs. This condition occurs because of the tree retentions in traditional gardens. Conservation actions need to be taken, namely maintaining trees vegetation, increasing reforestation, bench terraces use, mounds and mulch use. This condition also places traditional agroforestry as a sustainable land management system.